Development of Interactive E-Modules Based on Blender 3D Visualization: Analysis of Extraneous Cognitive Load and Its Effectiveness on Learning Outcome - Ashiddiqi, Mujahidin Abdillah; Hikmawan, Rizki; Romdhoni, Rhezwan Dhaifullah (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2026)
The growing demand for technology-based learning media has encouraged the development of interactive e-modules with three-dimensional visualization. However, poorly designed 3D media may increase extraneous cognitive load (ECL) and hinder students’ understanding. This study offers novelty by developing a 3D Blender-based interactive e-module designed with cognitive load management principles, particularly to minimize ECL while improving learning outcomes. The study aimed to develop the e-module and evaluate its impact on students’ cognitive load and achievement. This research used the Research and Development (R&D) method with the ADDIE model. The implementation involved 48 students at the University of Education Indonesia selected through purposive sampling using a one-group pretest-posttest design. Cognitive load was measured using a nine-item psychological scale questionnaire covering ICL, ECL, and GCL, while learning outcomes were assessed using a 15-item multiple-choice test. Data were analyzed descriptively and inferentially using the Shapiro-Wilk normality test and the Wilcoxon Signed Rank Test. The results showed that students’ ECL was low (x̄ = 2.09), indicating that the e-module did not overload working memory. Learning outcomes increased significantly from 34.67% to 84.67% (p = 0.000002). These findings indicate that the proposed e-module effectively supports conceptual understanding while reducing unnecessary cognitive load.